ANALISIS KESULITAN BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPS KELAS VIII - Rika Gustia; Aminuyati Aminuyati; Khosmas Khosmas (Universitas Tanjungpura, 2020)
Abstract This study aimed to determine the internal factors that caused learning difficulties, external factors that caused learning difficulties and the efforts to overcome learning difficulties in social sciences that are carried out by teachers, including the problems faced by grade VIII students at SMPN 04 Sungai Raya. This study was used a qualitative descriptive approach and descriptive methods. The subjects of this study were students of class VIII A at SMP N 04 Sungai Raya. The data collection techniques used were observation, interview and documentation. Data analysis techniques used were data reduction, data presentation and drawing conclusions. The results of this study indicate that: (1) the internal factors that cause students' learning difficulties include intelligence, attention, interest, self-confidence and learning habits. (2) external factors that cause students' learning difficulties include family factors, facilities and infrastructure factors and the environment around students (peers). (3) Efforts to overcome students' learning difficulties carried out by social studies subject teachers include reprimanding students who do not focus on learning, providing learning guidance, implementing remedials, providing motivation to raise enthusiasm in learning and giving assignments in order to make students learning independently at home. Keywords: Students' learning difficulties